Industrial Scale Production of Phytochemicals for Cancer Prevention: Challenges and Opportunities - Adam, Ansar Bilyaminu; Babanyaya, Abbas; Mustapha, Abdulkarim Babangida; Dwanga, Danladi Mudwa; Dalhatu, Abubakar; Bioltif, Yilni Edward; Abubakar, Musa Yahaya (Universitas Negeri Malang, 2024)
Phytochemicals, naturally occurring bioactive compounds in plants, have garnered significant attention for their potential role in cancer prevention. This review investigates the processes and methodologies for producing phytochemicals on an industrial scale. Key methods explored include advancements in green chemistry, synthetic biology, and nanotechnology to improve production efficiency and bioavailability. The research further analyzes challenges such as securing sustainable raw materials, maintaining consistent product quality, and navigating regulatory compliance. Drawing on case studies, the review highlights successful applications of phytochemicals in cancer prevention. By addressing these challenges through interdisciplinary research and collaborative innovation, this study underscores the potential of phytochemicals to contribute to cancer prevention strategies, public health improvement, and sustainable agricultural practices. Future directions prioritize optimizing commercialization pathways and leveraging technological advances to scale production.